2017
DOI: 10.12659/msm.904348
|View full text |Cite
|
Sign up to set email alerts
|

Left Univentricular Pacing by Rate-Adaptive Atrioventricular Delay in Treatment of Chronic Heart Failure

Abstract: BackgroundCardiac resynchronization therapy (CRT) is efficacious in the treatment of chronic heart failure (CHF); however, because it is non-physiological, some patients are unresponsive. The present study used rate-adaptive atrioventricular delay (RAAVD) to track the physiological atrioventricular delay and investigated the effects of left univentricular pacing on CRT.Material/MethodsPatients with CHF fulfilling the indication of CRT Class I were categorized into a left univentricular pacing by RAAVD group an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…Ten studies compared standard RAP (RAPON) with fixed rate pacing (RAPOFF) (Table 1) [5,12,22,29,[31][32][33][34][35][36]. Two studies were randomised control trials [12,29], while the remaining eight were cross over trials. In particular, the study conducted by Kass and colleagues [31] was suspended due to poor recruitment.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations
“…Ten studies compared standard RAP (RAPON) with fixed rate pacing (RAPOFF) (Table 1) [5,12,22,29,[31][32][33][34][35][36]. Two studies were randomised control trials [12,29], while the remaining eight were cross over trials. In particular, the study conducted by Kass and colleagues [31] was suspended due to poor recruitment.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…RAP sensors included accelerometers [21,30,32,33,36] and blended minute ventilation and accelerometers [31]. Six studies did not specify the sensor used [5,12,22,29,34,35].…”
Section: Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…It has also been explored for HF patients with CRT indications in developing countries with restricted resources where dual chamber pacemakers have been implanted with LV leads for patients with HF, LBBB and intact AV conduction. [ 86 ] This non-randomised study included 30 patients receiving LV univentricular pacemakers and showed non-inferiority by clinical and echo criteria but significant cost savings at 6 months versus standard BiV pacing with fixed AV intervals. AV delay optimisation was performed using echo and 10 ms decrements from the resting PR interval prior to initiating rate adaptive AV delay algorithms.…”
Section: The Role Of Mapping In Crtmentioning
confidence: 99%